Determination of Physico-Chemical Properties of Effluents from Soap Industry in Amravati - Mundhada, Sonal (Current Approaches in Science and Technology Research Vol. 13, 2021)
The present work is an attempt to examine the soap industrial effluents of Amravati region. Physicochemical Parameters of the effluents from soap industry of Amravati region had been analyzed. In this investigation Physico-Chemical Parameters such as colour, odour temperature, pH, electrical conductance, total dissolved solids, hardness of calcium and magnesium, chloride, COD, BOD, SAR, fluoride, Iron and alkalinity & sulphate had been analyzed of the effluent collected from the soap industry of Amravati region. Sodium and potassium elements were analyzed flame photo -metrically. It can be stated that the different studied physic-chemical parameter In which COD, pH, TDS, Sulphate ion Concentration fluoride & chloride Concentration exceeds than the WHO permissible limit the water needs to be treated before using it for domestic application.